XINJIANG AND ITS ROLE IN GREATER CENTRAL ASIAN REGIONAL ECONOMIC COOPERATION - Guang TIAN, Robert (CENTRAL ASIA AND THE CAUCASUS, 2009)
The Central Asia region mainly consists of the five Central Asian republics, namely Kazakhstan, the Kyrgyz Republic, Tajikistan, Turkmenistan, and Uzbekistan. The region is located in the center of the Eurasian continent. It borders to the north on the Russian Federation, to the south on Iran and Afghanistan, and to the east on the Xinjiang Uighur Autonomous Region of the People’s Republic of China (PRC). Mongolia lies in the upper portion of the PRC; while Azerbaijan, a member of the Caucasus, lies to the west of the region near Turkmenistan. Regional economic cooperation in Greater Central Asia1 started relatively late due to the allyearround war in Afghanistan and the regional conflicts in Central Asia after its countries gained their independence. Since the 1990s the Central Asian countries have shown great interest in regional economic cooperation and established certain mechanisms. Regional cooperation started with the five Central Asian countries signing the Agreement on Economic, Scientific-Technological, and Cultural Cooperation and developed into the establishment of the Central Asia Cooperative Organization2 in 2002. But generally speaking, these agreements have no substantial content and the efforts exerted in regional cooperation have resulted in few achievements. In recent years, as the war in Afghanistan subsided and economic development in Central Asia gained momentum, Greater Central Asian regional economic cooperation became a hot topic. According to the statistics of the Asian Development Bank, there are more than 20 regional cooperative development projects and programs in Central Asia for 2005-2008. The sponsor countries and international organizations include ADB—Asian Development Bank, CACO—Central Asia Cooperation Organization, CAREC— Central Asia Regional Economic Cooperation, CARECU—Central Asia Regional Economic Cooperation Unit, CMERF—CAREC Members Electricity Regulators Forum, EBRD—European Bank for Reconstruction and Development, ICT—information and communications technology, IMF—International Monetary Fund, MDGs—Millennium Development Goals, MI— multilateral institution, OIF—overall institutional framework, PRC—People’s Republic of China, RBR—regional business roundtable, RCSP—regional cooperation strategy and program, RCSPU— regional cooperation strategy and program update, RETA—regional technical assistance, SCO— Shanghai Cooperation Organization, SOM—senior officials’ meeting, TA—technical assistance, TIR—Transports Internationaux Routiers, and TPCC—Trade Policy Coordinating Committee.3 These cooperation mechanisms have different targets, different scopes of activity, and hence different priority areas. Xinjiang occupies a unique place in these regional cooperation programs and is a dynamically developing region, the economy of which is currently taking off. Although it does not strictly belong to Central Asia, as a minority autonomous region it is closely related to Central Asia and shares a total of 3,500 kilometers in common borders with Kazakhstan, Kyrgyzstan, Tajikistan, and Afghanistan. Xinjiang and the Central Asian region also have cultural and religious traditions in common and have always had close economic ties. The well-known Silk Road passed through Xinjiang and Central Asia. In recent years economic development in Xinjiang has been widely recognized and this area is destined to become the future economic outpost of China’s western region and Central Asia. Since the collapse of the U.S.S.R., as well as China’s reform and opening up to the outside world, the economic and trade relations between Xinjiang and the Central Asian countries have been expanding sharply, and there is no doubt that Xinjiang’s role in greater Central Asian regional economic cooperation will become very important in the near future.